توجيه القراءات القرآنية عند الإمام محمد الطاهر ابن عاشور دراسة تحليلية نقدية سورة البقرة -الآية- 51 -100 - سود بشيرة (university of eloued جامعة الوادي, 2025)
يقوم هذا البحث على دراسة توجيه القراءات القرآنية عند الإمام محمد الطاهر ابن عاشور دراسة نظرية تحليلية سورة البقرة -الآية- 51 -100، والذي يحمل في طياته السؤال الأساس: ما هي هذه الطرق والمسالك الغالبة في توجيه ابن عاشور للقراءات القرآنية؟ وهل سار على مسار من قبله أم حلل وناقش وانتقد توجيه من قبله؟ وهل أعمل قواعد الترجيح؟ وجاءت خطة البحث متضمنة لمقدمة وخاتمة وشقين، شق النظري وشق تطبيقي؛ الشق النظري: مبحث تمهيدي يتطرق إلى ترجمة المفسِّر وتفسيره، المبحث الأول: التعريف بمصطلحات التوجيه وما يتعلق به بصفة عامة، أما الشق التطبيقي يتضمن المبحث الثاني: يتحدث عن منهج ابن عاشور في توجيه القراءات في تفسيره وما يتعلق به بصفة خاصة، مع بعض الأمثلة من تفسيره، المبحث الثالث: عبارة عن أمثلة تطبيقية من سورة البقرة من الآية 51 إلى الآية 100 لابن عاشور في توجيه القراءات، مع خلاصة البحث. ومن أهم النتائج التي استخلصتها من البحث: كان لابن عاشور آراؤه المستقلة في توجيه القراءات، وهذا من خلال المواضع المدروسة؛ فقد حلل وناقش ورجح ووجه وأعمل القواعد وردّ بعض الآراء وقبل البعض الآخر. This research studies the interpretation of Qur'anic readings by Imam Muhammad Al-Tahir Ibn Ashur، through an inductive analysis of Surah Al-Baqarah، verses 51–100. The core question it seeks to answer is: What are the methods and approaches Ibn Ashur used in directing Qur'anic readings? did he examine ،debate and critique the advance of his predecessors or did he choose to follow their path? Did he apply the rules of preference (tarjeeh)? The research consists of an introduction، a conclusion and two sections which are theoretical and applied aspects . The theoretical one :initial portion discussing the interpreter's and the interpreted's translation ،the first chapter: definition of guidance terms and related concepts in general . The applied aspect includes the second section :he discusses Ibn Ashur's method of directing the readings in his interpretation ،how it pertains to this in particular and provides several examples from his interpretation . The third section : it consists of practical examples of Surah Al-Baqarah، verses 51-100 by IbnAshur in guiding the readings ، along with a summary of the research . The findings indicate that IbnAshur is not considered a follower if his predecessors ، but rather he exercised independent reasoning (ijtihad) and this was reflected in the studied topics ، debated، weighed opinions، applied rules، and accepted or rejected views as he saw fit.
مذكرة ماستر
Keywords: ابن عاشور توجيه القراءات سورة البقرة Ibn Ashur Drecting readings Surat al-Baqarah